Contribution to net zero emissions of integrating hydrogen production in wastewater treatment plants - Donald, Rickey; Boulaire, Fanny; Love, Jonathan G. (Journal of environmental management, 2023)
The reliability of renewable hydrogen supply for off-take applications is critical to the future sustainable energy economy. Integrated water electrolysis can be deployed at distributed municipal wastewater treatment plants (WWTP), creating opportunity for reduction in carbon emissions through direct and indirect use of the electrolysis output. A novel energy shifting process where the co-produced oxygen is compressed and stored to enhance the utilisation of intermittent renewable electricity is analysed. The hydrogen produced can be used in local fuel cell electric buses to replace incumbent diesel buses for public transport. However, quantifying the extent of carbon emission reduction of this conceptual integrated system is key. In this study, the integration of hydrogen production at a case study WWTP of 26,000 EP capacity and using the hydrogen in buses was compared with two conventional systems: the base case of a WWTP with grid electricity consumption offset by solar PV and the community's independent use of diesel buses for transport, and the non-integrated configuration with hydrogen produced at the bus refuelling location operated independently of the WWTP. The system response was analysed using a Microsoft Excel simulation model with hourly time steps over a 12-month time frame. The model included a control scheme for the reliable supply of hydrogen for public transport and oxygen to the WWTP, and considered expected reductions in carbon intensity of the national grid, level of solar PV curtailment, electrolyser efficiency and size of the solar PV system. Results showed that by 2031, when Australia's national electricity is forecast to achieve a carbon intensity of less than 0.186 kg CO2-e/kWh, integrating water electrolysis at a municipal WWTP for producing hydrogen for use in local hydrogen buses produced less carbon emissions than continuing to use diesel buses and offsetting emissions by exporting renewable electricity to the grid. By 2034, an annual reduction of 390 t–CO2–e is expected after changing to the integrated configuration. Considering electrolyser efficiency improvements and curtailment of renewable electricity, the reduction increases to 872.8 t–CO2–e. [Display omitted] •Integrated renewable hydrogen production with wastewater treatment and FCEBs.•New knowledge on reduced carbon emissions for integrated WWTP configurations.•Lower carbon emissions when integrating hydrogen and wastewater treatment.•Impact of electricity grid decarbonisation on integrated plant design.•Key design parameters identified to achieve net zero emissions.